Pharmacokinetic/Pharmacodynamic modeling and simulation of the effect of medications on β-amyloid aggregates and cholinergic neurocycle. (12th July 2019) - Awad, Asmaa; Fgaier, Hedia; Mustafa, Ibrahim; Elkamel, Ali; Elnashaie, Said
Highlights: The impact of Alzheimer's disease (AD) medications and levels of acetylcholine (ACh) and choline in the presynaptic and postsynaptic neurons is investigated. A mathematical tenth-dimensional nonlinear pharmacokinetics/pharmacodynamics (PK/PD) model was developed. Our analysis suggests that therapeutic agents inhibiting aggregation represent a likely successful approach to develop future trials and medications for AD. It is observed that the levels of β-amyloid aggregates decreased significantly with the increase of oral drug doses. Drugs such as galantamine that inhibit aggregation in the brain are likely to cause significant reduction in aggregates concentrations and increase in the levels of ACh and choline. Abstract: In this paper, a 10th order nonlinear pharmacokinetics/pharmacodynamics (PK/PD) model was developed to evaluate the impact of Alzheimer's disease (AD) medications such as galantamine on β-amyloid (βA) aggregates and levels of acetylcholine (ACh) and choline in the presynaptic (compartment 1) and postsynaptic (compartment 2) neurons based on the choline leakage hypothesis. The development is performed by incorporating a one-compartment PD/PK model into the two-enzyme/two-compartment model built by Mustafa et al., (2012a, b). The interaction between medications and βA aggregates is formulated based on a 6-h single oral dose of 2.5-10 mg of drugs which indicated PK/PD changes similar to the experimental findings obtained by Goh et al., (2011). Enhanced cholinergic behavior was observed in terms of a reduction in βA aggregates' concentrations and increase in the levels of ACh and choline in the pre-synaptic and postsynaptic neurons. The results indicate that therapeutic and pharmacological agents inhibiting βA aggregation represent a likely successful approach to develop future trials, new diagnostic techniques, and medications for AD. This study is helpful in developing experimental animal models to support the development of AD medications.